Valoración de los métodos de análisis de dentición mixta de Moyers y Tanaka- Johnston, en la predicción del diámetro mesiodistal de caninos y premolares no erupcionados (2014)
ABSTRACT: The objective of this study was to determine whether the methods of Moyers (M) percentile (p) 75, p85, p95 and Tanaka-Johnston (TJ), used in the prediction of the mesiodistal diameter of unerupted canines and premolars, either overestimate or underestimate their respective succedaneous diameter. Methods: diagnostic technology assessment in 56 plaster models of schoolchildren from Medellin, with class I skeletal and permanent erupted incisors, canines, and bicuspids, with follow-ups from 6 to 12 years of age. The teeth mesiodistal diameter was measured by the predictive methods of Tanaka-Johnston and Moyers p75, p85, p95. The predicted and actual values were evaluated by means of related Student’s t test and Wilcoxon test. These methods’ reproducibility was calculated by intraclass correlation coefficient (ICC) (95% CI), and their level was calculated using Bland-Altman 95% limits. Results: in the upper arch, significant actual value differences were observed with the T-J and Mp95 measurements. In the lower arch, the values of all the methods were different to the actual value (p > 0.05), except Mp75. Reproducibility was higher in the upper arch with T-J, followed by Mp85; in the lower arch, Mp75 was the method with the best reproducibility, followed by Mp85. In the upper arch, T-J overestimates the actual measurement by 0,333 mm in average (95% CI 2.100;1.434), and in the lower arch Mp75 overestimates by 2.14 (95% CI-2,020;1.592). Conclusion: the best predictive method for the upper arch is Tanaka-Johnston, and for the lower arch, Moyers at the 75th percentile; although both methods overestimate the actual value, they show adequate reproducibility.